The Effectiveness of Instagram Vlog in Teaching Speaking Achievement - Qurrotul Aini (FKDP (Forum Komunikasi Dosen Peneliti), 2024)
The research examines the use of Instagram Vlog in teaching speaking achievement. Vlogging, also known as video blogging, records videos to post information on a specific topic and post it to Instagram. According to the researcher, the researcher chose the one-group pretest-posttest design for pre-experimental research because it is the simplest design, requiring simply comparisons between pre-test and post-test. The finding shows that Instagram can affect students' speaking ability in the 6th grade of MI Assyafiiyah because there is a significant difference between this study's pre-test and post-test results. Static results using t-test showed that the pre-test and post-test results were -8,332 t-table with a significance level of 0.05, and df24 was 1.705. So the value of t count is greater than the value of t table -7.1320 > 2.0017, it can be concluded that Ha is accepted and Ho is rejected